2014
DOI: 10.1103/physrevb.90.085111
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous ferromagnetism and re-entrant magnetic glassiness in single-crystallineSm2Mo2O7

Abstract: We discuss the magnetic properties of a Sm2Mo2O7 single crystal as investigated by means of different experimental techniques. In the literature, a conventional itinerant ferromagnetic state is reported for the Mo 4+ sublattice below ∼ 78 K. However, our results of dc magnetometry, muon spin spectroscopy (µ + SR) and high-harmonics magnetic ac susceptibility unambiguously evidence highly disordered conditions in this phase, in spite of the crystalline and chemical order. This disordered magnetic state shares s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 130 publications
1
3
0
Order By: Relevance
“…Predictably, it should be noted that the lattice constant changes almost linearly with the radius.The magnetic behavior of all the samples under study was checked by dc magnetometry measured by a commercial dc-squid (MPMS2 by Quantum Device). The experimental results are shown in detail in the Supplementary Material S2 and confirm the typical magnetic behavior observed in these pyrochlore compounds[3,8,13,15,20]: a SG behavior for A = Er, Ho and Dy samples and a FM-like for the A = Gd sample. The EXAFS measurements were carried out at the Mo K-edge (20000 eV) in transmission geometry at the European Synchrotron Radiation Facility (ESRF) on beamline BM25A, using a double Si(111) crystal monochromator of the pseudo channel-cut type refrigerated at 200 K by a homemade ethanol cooling system.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Predictably, it should be noted that the lattice constant changes almost linearly with the radius.The magnetic behavior of all the samples under study was checked by dc magnetometry measured by a commercial dc-squid (MPMS2 by Quantum Device). The experimental results are shown in detail in the Supplementary Material S2 and confirm the typical magnetic behavior observed in these pyrochlore compounds[3,8,13,15,20]: a SG behavior for A = Er, Ho and Dy samples and a FM-like for the A = Gd sample. The EXAFS measurements were carried out at the Mo K-edge (20000 eV) in transmission geometry at the European Synchrotron Radiation Facility (ESRF) on beamline BM25A, using a double Si(111) crystal monochromator of the pseudo channel-cut type refrigerated at 200 K by a homemade ethanol cooling system.…”
supporting
confidence: 72%
“…Moreover, the transition of the magnetic state from FM to SG has been argued to be due to these competing double-exchange and superexchange interactions on the frustrated lattice [8,9]. It was also pointed out that both SG and FM components seem to coexist near the phase boundary of the corresponding phases [10,11], and a re-entrant transition of a SG type was observed at lower temperature and below T C , for A = Nd and Sm [11][12][13].…”
mentioning
confidence: 99%
“…One important finding common to several families of these oxides is that changes in r I , the ionic radius of the rare-earth ion R 3+ , gradually tune the local crystalline environment around the transition metal ion M 4+ and the overall electronic behaviour of the compound, accordingly. This is verified for M ions belonging to the 4d (e. g., Mo) [2,3] and 5d (e. g., Ir) [4][5][6][7] groups. Here, the characteristic temperature T MI for the development of a MIT (metal-toinsulator transition) is directly controlled by the average value r I related to a gradual R 1−x R ′ x substitution [8][9][10][11].…”
mentioning
confidence: 59%
“…However, it is believed that Mo pyrochlores are not dirty enough to host such a conventional spin glass 8 . Several experimental results indicated that there is a re-entrant spin-glass phase on the metallic side [24,28,29]. A fundamental question thus is what causes this apparently unconventional spin-glass state.…”
Section: Mo Pyrochlores a 2 Mo 2 Omentioning
confidence: 99%